Nutritional management of heart failure. Issue 3 (March 2023) - Kida, Keisuke; Miyajima, Isao; Suzuki, Norio; Greenberg, Barry H.; Akashi, Yoshihiro J.
Abstract: Nutrition in the cardiovascular field to date has focused on improving lifestyle-related diseases such as hypertension and diabetes from the viewpoint of secondary prevention. For these conditions, "nutrition for weight loss" is recommended, and nutritional guidance that restricts calories is provided. On the other hand, in symptomatic Stage C and D heart failure, it is known that underweight patients who manifest poor nutrition, sarcopenia, and cardiac cachexia have a poor prognosis. This is referred to as the "Obesity paradox". In order to "avoid weight loss" in patients with heart failure, a paradigm shift to nutritional management to prevent weight loss is needed. Rather than prescribing uniform recommendation for salt reduction of 6 g/day or less, awareness of the behavior change stage model is attracting attention. In this setting, the value of salt restriction will need to be determined to determine the priority level of intervention for undernutrition versus the need to prevent congestive signs and symptoms. In the Intensive Care Unit (ICU)/Cardiac Care Unit (CCU) for acute heart failure, nutritional intervention should be considered within 48 h of admission. Key points are selection of access route, timing of intervention, and monitoring of side effects. In nutritional management at home and in end-of-life care, food is a reflection of an individual's values, as well as a source of joy and encouragement. The importance of digestive tract should also be recognized in heart failure from oral flail to intestinal edema, constipation, and the intestinal bacteria called the heart-gut axis. Finally, we would like to propose a new term "heart nutrition" for nutritional management in patients with heart failure in this review. Compared to the evidence for exercise therapy in heart failure, studies assessing nutritional management remain scarce and there is a need for research in this area in the future. Graphical abstract: Unlabelled Image Highlights: In symptomatic heart failure, it is known that underweight is associated with poor prognosis and called "Obesity paradox". In the elderly, the salt restriction may lead to loss of appetite and reduced food intake, and the degree of priority of intervention for undernutrition must be determined and salt restriction may need to be lifted to determine the moderation. In the CCU for acute heart failure, nutritional intervention is required earlier, within 48 hours of admission, and the key points are the selection of access route, timing of intervention, and monitoring of side effects. The importance of the digestive tract should also be recognized in heart failure from oral flail to intestinal edema, constipation, and the intestinal bacteria called the Heart-Gut axis.